(untitled) (Universal International Scientific Journal, 2026)
This article provides information about the purpose and functions of acoustics, the study of all sounds and sounds produced by humans through the vocal apparatus, and the sources of sound. It is explained that acousticians should have a thorough knowledge of the timbre, pitch, vibration, amplitude, and acoustic resonators of each sound they produce. If the performance method guides the performance of sounds and images, the technical side helps to apply them to the performance, thus it sheds light on how the singing technique determines the musical performance. The development of the sense of feeling music, simultaneously with the singing technique, the importance of technique on the basis of musical material, that is, music pedagogy, is highlighted.